2008
DOI: 10.1007/s00415-008-5010-5
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson’s disease-related disorders in the impulsive-compulsive spectrum

Abstract: In Parkinson's disease (PD), there is increasing evidence for disorders in the impulsive-compulsive spectrum, related to the disease itself, to the pharmacological management of this disease or to both. These disorders comprise dopamine deficiency syndrome (with immediate reward seeking behaviour), dopamine dependency syndrome (with addictive behaviour), dopamine dysregulation syndrome (with both addictive behaviour and stereotyped behaviour) and impulse control disorders (such as pathological gambling, compul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 64 publications
2
39
1
1
Order By: Relevance
“…hoarding, shopping, eating, and gambling) [38][39][40]. People with PD must be advised of such risks when using smart glasses and caretakers and healthcare professionals should be vigilant of any addictive activities stemming from its use.…”
Section: Requirements and Constraintsmentioning
confidence: 99%
“…hoarding, shopping, eating, and gambling) [38][39][40]. People with PD must be advised of such risks when using smart glasses and caretakers and healthcare professionals should be vigilant of any addictive activities stemming from its use.…”
Section: Requirements and Constraintsmentioning
confidence: 99%
“…In a cross-sectional study on over 3,000 PD patients, ICDs were increased with a prevalence of 14% [5] . Pathological gambling (PG) as one presentation of ICD is reported in about 1.7-6% of DA-medicated patients [6][7][8][9][10][11][12][13] . While the first reports concerning PG were on PD patients under high doses of DA medication [10][11][12] , moderate doses [14] or low doses of DA [15] were also reported to cause sensitization towards ICD.…”
mentioning
confidence: 99%
“…Management primarily requires reducing or replacing dopamine receptor agonists [31,47]. In a 29-month follow-up study, 15 patients with ICDs showed remission or significant reduction of ICD without worsening motor symptoms after discontinuing or decreasing the dose of DA, balanced by an increase in levodopa treatment [31].…”
Section: Managementmentioning
confidence: 99%